Opportunities and Challenges for Constraint Programming - O’Sullivan, Barry (Proceedings of the AAAI Conference on Artificial Intelligence, 2021)
Constraint programming has become an important technology for solving hard combinatorial problems in a diverse range of application domains. It has its roots in artificial intelligence, mathematical programming, op- erations research, and programming languages. This paper gives a perspective on where constraint programming is today, and discusses a number of opportunities and challenges that could provide focus for the research community into the future.